Application of positive matrix factorization receptor model and elemental analysis for the assessment of sediment contamination and their source apportionment of Deepor Beel, Assam, India. (July 2020) - Dash, Siddhant; Borah, Smitom Swapna; Kalamdhad, Ajay S.
Graphical abstract: Highlights: First of its kind pollution source apportionment and elemental analysis for sediment samples of Deepor Beel. Geogenic, landfill, wastewater runoff and industrial effluents were the primary factors. Model was found to be highly reliable. Distorted structures of samples provided evidence of anthropogenic pollution. X-ray powder diffraction analysis provided evidences for anthropogenic contamination. Abstract: The present study is a first of its kind on the sediment contamination in Deepor Beel, which makes use of source apportionment receptor modelling technique {positive matrix factorization (PMF)} for determining and quantifying the sources' contribution to the pollution of the sediment column of Deepor Beel, Assam. Sediment samples were collected and analysed for seven different heavy metals from 23 sampling locations for a period from October 2017 to February 2019. Polling the entire dataset to a single matrix and carrying out multiple iterations revealed that four factors were optimum and thus, was applied for the simulation of the model. It was observed that the factors 1, 2, 3 and 4 corresponded to the soil parent material, leaching from the Boragaon landfill, discharge of agricultural and domestic wastes, and effluents from the industries and traffic emissions respectively. The sediment samples were further subjected to elemental analysis; X-ray powder diffraction (XRD) followed by Scanning electron microscope - Energy Dispersive X-Ray Spectroscopy (SEM – EDS), to determine the elemental composition and forms of heavy metals present in the sediment columns from various parts of the wetland. Sediment sample collected from the proximity of the landfill site was observed to be affected the most, probably due to leaching effects, especially during the monsoon. The central zone, however, was found to be devoid of any anthropogenic contaminations, while the sediment column near the industrial complex was found to be contaminated to a moderate extent. The study indicates the quantum of sediment contamination in the wetland and the causative parameters responsible, thus proving to be of immense help to the various governmental bodies in the planning and management of resources for sediment remediation of Deepor Beel.